What every library director should know - Curzon, Susan Carol (Rowman and Littlefield, 2014)
What Every Library Director Should Know is the insider's view of vital actions, behaviors and strategies to succeed in every type of library. The content is based both on the author's direct experience after a long career in several types of libraries but also on the direct observation of other managers. Inset into the book are pearls of wisdom from other directors, managers and observers who are answering the question, "what is the one piece of management wisdom that you would give to anyone who wishes to become a library director?" This book will help to get you there by explaining and illus.